CYCLIC VOLTAMMETRIC STUDIES FOR DIFFERENT SUBSTITUTED BENZILS - G, Nithya; Kanakam, Charles C; R, Sudha (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT The electroreduction of different substituted benzils was synthesized and studied in alcoholic and alkaline medium by cyclic voltammetry. In alkaline solutions, the reduction occurs in two reversible one-electron steps producing the anion radical and the dianion. In the presence of alcohol, the first reduction is unaffected and the second reduction wave becomes irreversible and is shifted toward positive potentials, following qualitatively the criteria for a rapid reaction of the dianion with the proton donor. The protonation can occur through the radical anion since it is not possible to observe the first step of the reaction to the radical anion. Keywords: Cyclic voltammetric studies, Synthesized benzils, Electroanalysis.